A single immunization with H5N1 virus-like particle vaccine protects chickens against divergent H5N1 influenza viruses and vaccine efficacy is determined by adjuvant and dosage - Dexin Kong; Yanjuan He; Jiaxin Wang; Lanyan Chi; Xiang Ao; Hejia Ye; Weihong Qiu; Xiutong Zhu; Ming Liao; Huiying Fan (Emerging Microbes and Infections)
The H5N1 subtype highly pathogenic avian influenza virus (HPAIV) reveals high variability and threatens poultry production and public health. To prevent the spread of H5N1 HPAIV, we developed an H5N1 virus-like particle (VLP) vaccine based on the insect cell-baculovirus expression system. Single immunization of the H5N1 VLP vaccines induced high levels of HI antibody titres and provided effective protection against homologous virus challenge comparable to the commercial inactivated vaccine. Meanwhile, we assessed the relative efﬁcacy of different adjuvants by carrying out a head-to-head comparison of the adjuvants ISA 201 and ISA 71 and evaluated whether the two adjuvants could induce broadly protective immunity. The ISA 71 adjuvanted vaccine induced significantly higher levels of Th1 and Th2 immune responses and provided superior cross-protection against antigenically divergent H5N1 virus challenge than the ISA 201 adjuvanted vaccine. Importantly, increasing the vaccine dose could further enhance the cross-protective efficacy of H5N1 VLP vaccine and confer completely sterilizing protection against antigenically divergent H5N1 virus challenge, which was mediated by neutralizing antibodies. Our results suggest that the H5N1 VLP vaccine can provide broad-spectrum protection against divergent H5N1 influenza viruses as determined by adjuvant and vaccine dose.